2020
DOI: 10.2340/00015555-3466
|View full text |Cite
|
Sign up to set email alerts
|

Skin Infections Caused by Staphylococcus aureus

Abstract: Staphylococcus aureus is the most common pathogen involved in skin infections worldwide, regardless of the patient’s age, the climate or geographical area. The main skin clinical manifestations can be linked to a few toxins produced by the bacteria, which give rise to a rich and varied clinical spectrum. Panton Valentine leucocidin, exfoliatins, enterotoxins and toxin shock syndrome toxin 1 are the main toxins involved in most dermatological manifestations associated with S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 77 publications
0
43
0
5
Order By: Relevance
“…Bacterial infections are the result of pathogenic bacteria entering and multiplying in the human body; these are a major deleterious factor in some infections ( Anderson and Kendall, 2017 ; Martin and Bachman, 2018 ). For example, the gram-positive bacterium Staphylococcus aureus is a human pathogen ( Kimmig et al, 2021 ) that is constantly a source of skin infections, lung infections, gastroenteritis, and urinary tract infections ( Thomer et al, 2016 ; Del Giudice, 2020 ). Over the years, researchers have observed that antibacterial substances can be isolated from endophytic fungi of various medicinal plants ( Pinheiro et al, 2017 ; Nischitha and Shivanna, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infections are the result of pathogenic bacteria entering and multiplying in the human body; these are a major deleterious factor in some infections ( Anderson and Kendall, 2017 ; Martin and Bachman, 2018 ). For example, the gram-positive bacterium Staphylococcus aureus is a human pathogen ( Kimmig et al, 2021 ) that is constantly a source of skin infections, lung infections, gastroenteritis, and urinary tract infections ( Thomer et al, 2016 ; Del Giudice, 2020 ). Over the years, researchers have observed that antibacterial substances can be isolated from endophytic fungi of various medicinal plants ( Pinheiro et al, 2017 ; Nischitha and Shivanna, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Empiric antibiotic such as Trimethoprim-Sulfamethoxazole or Doxycycline is recomended for moderate purulent SSTIs and Vancomycin or Daptomycin for severe purulent SSTIs. 9,10 In this case, the location of abscesses is on the face area and there was systemic signs of infection such as fever, increase heart rate, fatigue and increased leukocyte count (neutrophil dominant) so it classified to moderate purulent SSTIs. We did incision and drainage for the abscesses and continued with pus culture and sensitivity test to identify the microbe and determine the antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus is one of the main biofilm-forming pathogens found on the skin. This strain is an opportunistic microbe that can generate abscesses, cellulitis, folliculitis, and lymphangitis [31]. The drug-resistant S. aureus has a high probability of establishing a biofilm for developing into persistent and recurrent infections [9].…”
Section: Cutaneous Microbiomementioning
confidence: 99%